Supportive, transformative and reverse effects of media on Tunisian diaspora's political identity. (1st April 2020) - Shehata, Mostafa
The Tunisian diaspora in Europe has gained significant research interest due to the fundamental changes recently triggered by the Tunisian Revolution with which the diaspora strongly interacted. This article investigates the potential effects of media use on the political identity of Tunisian diasporic communities in Europe, from a sociopolitical communication perspective. Based on 45 interviews conducted with Tunisians living in Denmark, Sweden and France, a special focus has been set on the patterns of media use in relation to components of political identity (homeland orientation, religion and ideology), considering the combined influences of both country of origin and country of residence. The analysis shows that media exerted supportive effects on the diaspora's homeland orientations – a process that likely depended on participants' previous connection with Tunisia. The media also exerted short-term transformative effects on the political ideology and a reverse effect on religious orientations – a process that mainly depended on life in both country of origin and country of residence. This article proposes that this Tunisian diaspora is more likely to construct a hybrid identity, supported by media channels that facilitate the adoption of sociopolitical principles derived from both country of origin and country of residence.